PHYTOSSOCIOLOGICAL ASPECTS OF FRAGMENT OF DECIDUAL SEASONAL FOREST, SANTA MARIA, RS - Longhi, Solon Jonas (2000)
This  work  aimed  at  studying the  vegetation  in a fragment of  Deciduous  Seasonal Forest under successional process, in an area of the Tabor Association (29043’ S; 53047’ W), municipal district of Santa Maria, RS, Brazil. Sixteen sample units (10x20m) were systematically located in the area to allow the recording (measurement and indentification) of individual plants with a Circumference at Breast Height equal to or larger than 30cm. Sampling was also carried out in circular units with radii of 1,78m to count up and identify the regeneration (individual with CBH smaller than 30 cm). The occurrence of 64 species of trees and shrubs comprising 54 genera and 31 botanical families was observed. The most important species were Myrocarpus frondosus, Cupania vernalis, Ocotea puberula, Patagonula americana, Casearia sylvestris, Luehea divaricata, Enterolobium contortisiliquum and Helietta apiculata. In the regeneration the species with higher density of individuals were Trichilia elegans, Nectandra megapotamica, Actinostemon concolor, Piper gaudichaudianum, Cupania vernalis, Hybanthus bigibbosus, Aiouea saligna and Parapiptadenia rigida. It was demonstrated the evidence of a continuous successional process, through the replacement of species in the several strata of the forest, with some well represented from the regeneration up to the higher forest stratum.